Time Course of Recovery Following Resistance Exercise with Different Loading Magnitudes and Velocity Loss in the Set - Fernando Pareja-Blanco; Antonio Villalba-Fernández; Pedro J. Cornejo-Daza; Juan Sánchez-Valdepeñas; Juan José González-Badillo (MDPI AG, 2019)
The aim of this study was to compare the time course of recovery following four different resistance exercise protocols in terms of loading magnitude (60% vs. 80% 1RM—one-repetition maximum) and velocity loss in the set (20% vs. 40%). Seventeen males performed four different protocols in full squat exercise, which were as follows: (1) 60% 1RM with a velocity loss of 20% (60-20), (2) 60% 1RM with a velocity loss of 40% (60-40), (3) 80% 1RM with a velocity loss of 20% (80-20), and (4) 80% 1RM with a velocity loss of 40% (80-40). Movement velocity against the load that elicited a 1 m·s−1 velocity at baseline measurements (V1-load), countermovement jump (CMJ) height, and sprint time at 20 m (T20) were assessed at Pre, Post, 6 h-Post, 24 h-Post, and 48 h-Post. Impairments in V1-load were significantly higher for 60-40 than other protocols at Post (p < 0.05). The 60-20 and 80-40 protocols exhibited significant performance impairments for V1-load at 6 h-Post and 24 h-Post, respectively (p < 0.05). CMJ height remained decreased for 60-20 and 60-40 until 24 h-Post (p < 0.001–0.05). Regarding T20, the 80-40 protocol resulted in higher performance than 60-40 at 24 h-Post and the 80-20 protocol induced a greater performance than 60-40 protocol at 48 h-Post (p < 0.05). A higher velocity loss during the set (40%) and a lower relative load (60% 1RM) resulted in greater fatigue and slower rate of recovery than lower velocity loss (20%) and higher relative load (80% 1RM).